2022
DOI: 10.1182/bloodadvances.2022007676
|View full text |Cite
|
Sign up to set email alerts
|

The impact of race, ethnicity, and obesity on CAR T-cell therapy outcomes

Abstract: Cancer outcomes with chemotherapy are inferior in patients of minority racial/ethnic groups and those with obesity. Chimeric antigen receptor (CAR) T-cell therapy has transformed outcomes for relapsed/refractory hematologic malignancies, but whether its benefits extend commensurately to racial/ethnic minorities and patients with obesity is poorly understood. With a primary focus on patients with B-cell acute lymphoblastic leukemia (B-ALL), we retrospectively evaluated the impact of demographics and obesity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Further research is warranted to fully understand the contribution of genetic variation to this disparity in ALL incidence and how this can impact other clinical endpoints beyond the risk of developing ALL that demonstrate racial/ethnic disparities, such as overall survival, risk of relapse, and cytokine release syndrome with chimeric antigen receptor T cell therapy. 4 , 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Further research is warranted to fully understand the contribution of genetic variation to this disparity in ALL incidence and how this can impact other clinical endpoints beyond the risk of developing ALL that demonstrate racial/ethnic disparities, such as overall survival, risk of relapse, and cytokine release syndrome with chimeric antigen receptor T cell therapy. 4 , 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, Spanish‐speaking patients may have been excluded from studies evaluating these regimens, even though census data reports that Hispanics make up the second largest ethnic group after Non‐Hispanic Whites 25,26 . In some pediatric leukemia clinical trials, disparities have been demonstrated in degrees of enrollment as well, with Hispanic and Non‐Hispanic Black patients enrolled to a lesser degree than Non‐Hispanic White patients 25,27 . Winestone et al demonstrated that early mortality was actually decreased among patients enrolled on a clinical trial, compared with those unenrolled 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics are underrepresented in clinical trials in ALL/ALLy, with those speaking Spanish possibly at a larger disadvantage than those speaking English because some trials lack Spanish informed consent documents. Thus, Spanish‐speaking patients may have been excluded from studies evaluating these regimens, even though census data reports that Hispanics make up the second largest ethnic group after Non‐Hispanic Whites 25,26 . In some pediatric leukemia clinical trials, disparities have been demonstrated in degrees of enrollment as well, with Hispanic and Non‐Hispanic Black patients enrolled to a lesser degree than Non‐Hispanic White patients 25,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, few studies of CAR T-cell therapy in RRMM or other cancer types have investigated racial and ethnic differences in adverse events and outcomes in the SOC setting. 15 , 16 , 19 , 20 , 21 To address this limitation, the goal of this study was to evaluate the safety and efficacy of ide-cel by race and ethnicity among patients with RRMM treated with SOC CAR T-cell therapy. To the best of our knowledge, this is the first investigation of potential racial and ethnic differences among recipients of SOC ide-cel CAR T-cell therapy for RRMM.…”
Section: Introductionmentioning
confidence: 99%